Atomic-scale insights into electro-steric substitutional chemistry of cerium oxide. Issue 38 (24th September 2020) - Zhang, Haiwu; Castelli, Ivano E.; Santucci, Simone; Sanna, Simone; Pryds, Nini; Esposito, Vincenzo
Abstract : Atomic-scale simulations identify the substitutional chemistry of cerium oxide beyond the trivalent, rare-earth cations. Abstract : Cerium oxide (ceria, CeO2 ) is one of the most promising mixed ionic and electronic conducting materials. Previous atomistic analysis has widely covered the effects of substitution on oxygen vacancy migration. However, an in-depth analysis of the role of cation substitution beyond trivalent cations has rarely been explored. Here, we investigate soluble monovalent (Li +, Na +, K +, Rb + ), divalent (Fe 2+, Co 2+, Mn 2+, Mg 2+, Ni 2+, Zn 2+, Cd 2+, Ca 2+, Sr 2+, Ba 2+ ), trivalent (Al 3+, Fe 3+, Sc 3+, In 3+, Lu 3+, Yb 3+, Y 3+, Er 3+, Gd 3+, Eu 3+, Nd 3+, Pr 3+, La 3+ ) and tetravalent (Si 4+, Ge 4+, Ti 4+, Sn 4+, Hf 4+, Zr 4+ ) cation substituents. By combining classical simulations and quantum mechanical calculations, we provide an insight into defect association energies between substituent cations and oxygen vacancies as well as their effects on the diffusion mechanisms. Our simulations indicate that oxygen ionic diffusivity of subvalent cation-substituted systems follows the order Gd 3+ > Ca 2+ > Na + . With the same charge, a larger size mismatch with the Ce 4+ cation yields a lower oxygen ionic diffusivity, i.e., Na + > K +, Ca 2+ > Ni 2+, Gd 3+ > Al 3+ . Based on these trends, we identify species that could tune the oxygen ionic diffusivity: we estimate that the optimum oxygen vacancy concentration for achieving fast oxygen ionic transport is ≈2.5% for Gd x Ce1− x O2− x /2, Ca x Ce1− x O2− x and Na x Ce1− x O2−3 x /2 at 800 K. Remarkably, such a concentration is not constant and shifts gradually to higher values as the temperature is increased. We find that co-substitutions can enhance the impact of the single substitutions beyond that expected by their simple addition. Furthermore, we identify preferential oxygen ion migration pathways, which illustrate the electro-steric effects of substituent cations in determining the energy barrier of oxygen ion migration. Such fundamental insights into the factors that govern the oxygen diffusion coefficient and migration energy would enable design criteria to be defined for tuning the ionic properties of the material, e.g., by co-substitutions.